Предмет: Алгебра,
автор: mkviktorivna0
Розв'яжіть рiвняння -(х-2)(2-x)=(x+4)(x-1)-x
Ответы
Автор ответа:
3
Ответ:
-(х-2)(2-х)=(х+4)(х-1)-х
-(2х-х²-4+2х)= х²- х +4х - 4 -х
-(4х-х²-4) = х² + 2х -4
-4х+х²+4=х²+2х-4
-4х+4=2х-4
-4х-2х=-4-4
-6х=-8
х=4/8 = 1 1/3
Объяснение:
надеюсь помогла)
Похожие вопросы
Предмет: Русский язык,
автор: dmitrijperesypkin37
Предмет: Геометрия,
автор: qudksssss
Предмет: Биология,
автор: Drakonchek282
Предмет: Алгебра,
автор: aleksandrpuskin875
Предмет: Физика,
автор: bogomaz2007